Multiple recombination sites at the 5′-end of murine coronavirus RNA - Keck, James G. (Virology, 1987)
Mouse hepatitis virus (MHV), a murine coronavinus, contains a nonsegmented RNA genome. We have previously shown that MHV could undergo RNA-RNA recombination in crosses between temperature-sensitive mutants and wild-type viruses at a very high frequency (S. Makino, J. G. Keck, S. A. Stohlman, and M. M. C. Lai (1986)J. Virol. 57, 729–737). To better define the mechanism of RNA recombination, we have performed additional crosses involving different sets of MHV strains. Three or possibly four classes of recombinants were isolated. Recombinants in the first class, which are similar to the ones previously reported, contain a single crossover in either gene A or B, which are the 5′-most genes. The second class of recombinants contain double crossovers in gene A. The third class of recombinants have crossovers within the leader sequence located at the 5′-end of the genome. The crossover sites of the third class have been located between 35 and 60 nucleotides from the 5′-end of the leader RNA. One of these recombinants has double crossovers within the short region comprising the leader sequences. Finally, we describe one recombinant which may contain a triple crossover. The presence of so many recombination sites within the 5′-end of the genome of murine coronaviruses confirms that RNA recombination is a frequent event during MHV replication and is consistent with our proposed model of “copy-choice” recombination in which RNA replication occurs in a discontinuous and nonprocessive manner.